Efektivitas Feedback pada Asesmen Formatif melalui Quizizz terhadap Penguasaan Konsep dan Motivasi Belajar Siswa pada Materi Sistem Pencernaan: (The Effectiveness of Feedback in Formative Assesment Using Quizizz on Students’ Concept Mastery and Learning Motivation in the Digestive System Topic) - Rafifah, Rifa; Sriyati, Siti; Saefudin, Saefudin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Biology learning requires a comprehensive understanding of concepts, including the relationships among organ structures, digestive processes, enzyme functions, and disorders of the human digestive system. This study aimed to analyze the effectiveness of descriptive feedback provided through Quizizz-based formative assessment in improving students’ conceptual mastery and learning motivation. A pre-experimental research design was employed, involving 33 Grade 11 science students from a public senior high school in Bogor City. Data on conceptual mastery were collected through tests administered for each subtopic, while learning motivation was measured using a five-point Likert-scale questionnaire administered before and after the intervention. The results showed that the attainment of the Minimum Mastery Criterion (KKM) was uneven across the subtopics. The subtopic of digestive system disorders or abnormalities significantly met the KKM, with a significance value of 0.000. In contrast, the subtopics of the structure and function of digestive organs, mechanical and chemical digestive processes, and the role of enzymes did not show significant attainment. The students’ mean conceptual mastery score was 81.03, with 60.61% of the students meeting the KKM and 39.39% not meeting it. Although the effectiveness based on the KKM was not statistically significant, students’ learning motivation increased significantly from 2.68 to 3.86 on a five-point Likert scale. Therefore, descriptive feedback provided through Quizizz can support students’ conceptual mastery and enhance their learning motivation, although its effectiveness based on the KKM remains uneven. Abstrak. Efektivitas feedback deskriptif otomatis dalam asesmen formatif berbantuan Quizizz menjadi fokus dalam penelitian ini, khususnya terhadap penguasaan konsep dan motivasi belajar siswa pada materi sistem pencernaan manusia. Penelitian dilaksanakan dengan metode pre-eksperimen menggunakan desain one-group pretest-posstest. Sebanyak 33 siswa kelas XI dari salah satu MA Negeri di Kota Bogor. Pengumpulan data dilakukan melalui tes penguasaan konsep serta angket motivasi belajar dengan skala Likert 5 poin. Data yang terkumpul dianalisis secara deskriptif dan inferensial, lalu dikaji berdasarkan ketercapaian Kriteria Ketuntasan Minimal (KKM). Temuan penelitian menunjukkan bahwa penggunaan feedback deskriptif otomatis melalui Quizizz pada asesmen formatif mampu meningkatkan penguasaan konsep dan motivasi belajar siswa. Hal tersebut terlihat dari kenaikan rata-rata skor penguasaan konsep pada setiap submateri. Meski demikian, jika mengacu pada Kriteria Ketuntasan Minimal (KKM), hasil peningkatan belum sepenuhnya optimal karena ketuntasan belum tercapai pada seluruh submateri. Rata-rata motivasi belajar siswa juga mengalami kenaikan, dari 2,68 menjadi 3,86. Pada skala Likert 1-5. Oleh karena itu, feedback deskriptif otomatis berbantuan Quizizz dapat dimanfaatkan sebagai alternatif untuk menunjang penguasaan konsep dan motivasi belajar siswa pada materi sistem pencernaan manusia.